(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
In this study, phthalonitrile derivative was prepared by a nucleophilic substitution reaction of 3-nitrophthalonitrile in the presence of K2CO3 as a base in a non-aqueous organic solvent. Cyclotetramerization of phthalonitrile in the presence of metal salt, Ni(II)) gave peripherally substituted metal phthalocyanine complexes. The structure of the synthesized compounds was characterized by different analytical tools such as 1H NMR, UV-Vis, and FT-IR spectrophotometry and cyclic voltammetry. The disappearance of the C≡N stretching vibration from the IR spectra of phthalonitrile was observed at 2230 cm−1. The FTIR vibration results for C=O, C=C and C-O were 1712cm-1, 1615 cm-1 and 1276 cm-1 respectively. Solubility of metal phthalocyanine complexes was found to be very low in common laboratory solvents such as tetrahydrofuran (THF) and dimethylformamide (DMF). The electronic spectrum of NiPc in dimethylformamide (DMF) showed intense Q absorption at 690 nm. UV-Vis spectra of phthalocyanines showed electronic spectra with two strong absorption bands, Q and B bands. The Q band was found in 600–750 nm and B at 300–400 nm for both. The thermal stability of the phthalocyanine derivative was checked by T.G.A and the degradation was observed to start at 309 oC, which showed that the complex could withstand relatively high temperature. It could therefore be concluded that the metal phthalocyanine prepared in this study showed suitably high thermal stability and can be used for various applications